Pola Asuh Ibu Berhubungan dengan Status Gizi Bayi Usia 12-24 Bulan di Puskesmas Siborongborong - Siregar, Eka Darmayanti Putri; Rini Angraini (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Nutritional problems in children are one of the priority problem to be solved. The children in this problem not only harmed their health nowadays but also their future. Undernutrition was affected by multifactorial such as the mother's parenting style. Our study aimed to know the association of mother parenting style with the nutritional status of children aged 12-24 months in Siborongborong Public Health Center. This cross-sectional study conducted on June-July 2024. Sampling method was purposive sampling with 30 children aged 12-24 month. The data was collected by interviewing the mother of the children and measuring children's anthropometrics and the instruments were Parenting Style and Dimension Questionnaire (PSDQ) and digital scales for children. Data was analyzed with Chi-Square (p<0,05). There were 26 children (86,7%) in good maternal parenting style and 4 children (13,3%) in not a good maternal parenting style. Children with normal nutritional status were 27 (90%) and 3 (10%) undernutrition. One child (25%) had a good maternal parenting style and normal nutritional status otherwise 3 (75%) in not a good maternal parenting style and undernutrition. Our study found there was an association between maternal parenting style with nutritional status on children aged 12-24 months in Siborongborong Public Health Center (p=0,034). The medical staff always should give the health information focused on maternal parenting style as the way to cut nutritional problem and extend the better nutritional status of children.